2009
DOI: 10.2337/db09-1197
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Lactation and Incidence of the Metabolic Syndrome in Women of Reproductive Age According to Gestational Diabetes Mellitus Status: A 20-Year Prospective Study in CARDIA (Coronary Artery Risk Development in Young Adults)

Abstract: OBJECTIVEThe objective of the study was to prospectively assess the association between lactation duration and incidence of the metabolic syndrome among women of reproductive age.RESEARCH DESIGN AND METHODSParticipants were 1,399 women (39% black, aged 18–30 years) in the Coronary Artery Risk Development in Young Adults (CARDIA) Study, an ongoing multicenter, population-based, prospective observational cohort study conducted in the U.S. Women were nulliparous and free of the metabolic syndrome at baseline (198… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

14
192
2
14

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 229 publications
(222 citation statements)
references
References 42 publications
14
192
2
14
Order By: Relevance
“…Many studies have reported that longer duration of breastfeeding may reduce long‐term risk of cardiovascular markers including hypertension, hyperlipidemia, and metabolic syndrome 32, 33, 34, 35, 36, 37, 47. Few studies have measured cardiovascular markers longitudinally from time of breastfeeding to menopause, and those that have are observational studies that are limited to self‐reported disease outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have reported that longer duration of breastfeeding may reduce long‐term risk of cardiovascular markers including hypertension, hyperlipidemia, and metabolic syndrome 32, 33, 34, 35, 36, 37, 47. Few studies have measured cardiovascular markers longitudinally from time of breastfeeding to menopause, and those that have are observational studies that are limited to self‐reported disease outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Research findings point to the protective effect of breastfeeding on maternal health including a reduced risk of breast cancer and ovarian cancer and improved cardiovascular health 29, 30, 31. Women who report more than 9 cumulative months of breastfeeding over their reproductive lifetime are less likely to develop hypertension, hyperlipidemia, and metabolic syndrome 32, 33, 34, 35, 36, 37. Further, evidence suggests that a longer duration of breastfeeding is associated with a lower risk of developing type 2 diabetes mellitus,38, 39, 40, 41, 42, 43 and reduced maternal postpartum weight 44, 45, 46, 47…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such pregnancy‐related cardiometabolic changes may reverse more quickly and more completely with breastfeeding, with several studies reporting that women who breastfeed have more favorable cardiometabolic profiles compared with women who do not breastfeed 3, 4, 5. Longer breastfeeding duration has also been associated with a lower risk of metabolic syndrome,6 hypertension,7, 8 and diabetes mellitus in later life,9 which may lead to long‐term protective benefits for cardiometabolic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…По-казано, что большое количество беременностей и родов повышает риск развития МС [6,7] независимо от нали-чия ожирения до беременности и увеличения массы тела во время беременности. Наоборот, более длительное грудное вскармливание ассоциировано с низким рис-ком МС [6,8]. Наличие гестационного диабета или НТГ при беременности являются факторами риска разви-тия МС в течение трех месяцев после родов [9].…”
unclassified